Histones, DNA, and Citrullination Promote Neutrophil Extracellular Trap Inflammation by Regulating the Localization and Activation of TLR4 - Theodora-Dorita Tsourouktsoglou; Annika Warnatsch; Marianna Ioannou; Dennis Hoving; Qian Wang; Venizelos Papayannopoulos (Cell Reports, 2020)
Summary: Neutrophil extracellular traps (NETs) promote atherosclerosis by inducing proinflammatory cytokines, but the underlying mechanism remains unknown. NET DNA is immunogenic, but given the cytotoxicity of NET histones, it is unclear how it activates cells without killing them. Here, we show that histones, DNA, citrullination, and fragmentation synergize to drive inflammation below the histone cytotoxicity threshold. At low concentrations, nucleosomes induce cytokines, but high concentrations kill cells before cytokines are produced. The synergy between histones and DNA is critical for sub-lethal signaling and relies on distinct roles for histones and DNA. Histones bind and activate TLR4, whereas DNA recruits TLR4 to histone-containing endosomes. Citrullination is dispensable for NETosis but potentiates histone-mediated signaling. Consistently, chromatin blockade or PAD4 deficiency reduces atherosclerosis. Inflammation is also reduced in infected mice expressing GFP-tagged histones that block TLR4 binding. Thus, chromatin promotes inflammation in sterile disease and infection via synergistic mechanisms that use signals with distinct functions.